Strategi Pengembangan Industri Berbasis Maritim Berdasarkan Sumber Daya, Peran, dan Posisi Daerah (Studi Kasus: Kalimantan Utara) - Boby Rahman (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
North Kalimantan is a new province, previously a part of East Kalimantan province, that has potential in the marine and fishery sector. The marine and fishery sector has potential to contribute to the regional economy and is expected to bring economic improvement throughout the region equally and evenly. Through SWOT analysis, this study examines to discover maritime-based industrial development strategies by considering existing resources, and location’s potential in area role and position distribution. The result of analysis divides area development into two main concepts of maritime-based industrial development, which are maritime raw-material industry area development and product distribution industry area development, where if connected with an imaginary line will form a development area triangle.